2021
DOI: 10.1097/iae.0000000000002939
|View full text |Cite
|
Sign up to set email alerts
|

Multifocal Electroretinography and Spectral-Domain Optical Coherence Tomography in Macula-Off Rhegmatogenous Retinal Detachment

Abstract: Purpose:To analyze the temporal trends in structural changes using spectral-domain optical coherence tomography and functional changes using multifocal electroretinogram after rhegmatogenous retinal detachment surgery.Methods: This prospective cohort study enrolled 69 patients with macula-off rhegmatogenous retinal detachment who underwent successful surgery. Early Treatment Diabetic Retinopathy Study visual acuity, multifocal electroretinogram evaluation of the central 5°, and spectral-domain optical coherenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…ERG responses may gradually decrease if SO remains in the vitreous cavity for a long time [46]. We should consider that photoreceptor recovery after retinal reattachment requires approximately 4 weeks [17,[47][48][49]. In our series, the SO tamponade duration was shorter than 9 months but significantly longer than 4 weeks (mean [SD]: 147.8 [34.9] days).…”
Section: Discussionmentioning
confidence: 76%
See 4 more Smart Citations
“…ERG responses may gradually decrease if SO remains in the vitreous cavity for a long time [46]. We should consider that photoreceptor recovery after retinal reattachment requires approximately 4 weeks [17,[47][48][49]. In our series, the SO tamponade duration was shorter than 9 months but significantly longer than 4 weeks (mean [SD]: 147.8 [34.9] days).…”
Section: Discussionmentioning
confidence: 76%
“…A few studies have demonstrated early deterioration with a lasting effect on ERG amplitude after SO injection [17,20,35]. A study suggested retinal degeneration or a nerve impulse insulating effect due to the presence of intravitreal SO [20].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations